Physical Couple and Family Violence Among Clients Seeking Therapy: Identifiers and Predictors - Zahl-Olsen, Rune; Gausel, Nicolay; Zahl-Olsen, Agnes; Bertelsen, Thomas Bjerregaard; Haaland, Aashild Tellefsen; Tilden, Terje (Frontiers in Psychology, 2019)
Introduction: Couple violence affects many, and the consequences of those actions are grave, not only for the individual suffering at the hand of the perpetrator but also for the other persons in the family. Violence often happens among more than just the adults within one family. Even if couple violence has been thoroughly investigated in the general population very few studies have investigated this objective on a clinical sample, and none of these have included family violence. Aim: This article identifies and describes the group of clients that have issues of physical couple and family violence. It analyses a model that can help to discover physical violence and help therapists to assess what actions to take in therapy to prevent further physical violence Methodology: Descriptive analysis, t-tests and structural equation modeling (SEM) are used on a sample of clients receiving couple and family therapy in Norway (N=830). Family violence is modeled by the partner's expectations towards each other, levels of anger, sexual satisfaction and self-control. Results: One-in-five clients experienced physical couple violence in their current relationship and one-in-four experienced physical family violence. The group of clients that experienced couple violence differed from those without such experiences in having lower income, more prior experience with psychotherapy, more experience with alcohol abuse in childhood, and far more physical family violence in their current family. Our model predicting physical couple and family violence explained as much as 53% of family violence and had three positive, significant predictors (expectation, anger, and sexual satisfaction) and one, significant negative predictor (self-control). Somewhat unexpected, sexual satisfaction was a positive, and not a negative, predictor of violence. Conclusion: Our study identified one-in-four clients in couple and family therapy experience physical couple violence. Unreasonable expectation from one partner towards the other, anger and sexual satisfaction were positive predictors of physical violence, while self-control was found to be a negative predictor of physical violence. Implications for therapeutic work and the prevention of physical violence is discussed.